Strategy in Point Voting: Comment - Mueller, Dennis C. (Quarterly Journal of Economics, 1977)
Journal Article Strategy in Point Voting: Comment Get access Dennis C. Mueller Dennis C. Mueller International Institute of Management, Berlin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 91, Issue 3, August 1977, Page 509, https://doi.org/10.2307/1885982 Published: 01 August 1977